Pertumbuhan Bibit Kakao terhadap Aplikasi Pupuk Kitosan dengan Berbagai Konsentrasi - Najmah Shabah; Iis Purnamawati; Edi Wiraguna (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
This study aimed to evaluate the effect of chitosan-based liquid organic fertilizer (LOF) at various concentrations on the growth of cocoa seedlings (Theobroma cacao L.). The research was conducted at PTPN I Regional 5, Kendenglembu Plantation, Banyuwangi, for four months using a Completely Randomized Block Design (RCBD) with five treatments: P0 (control), P1 (10 mL/L), P2 (20 mL/L), P3 (30 mL/L), and P4 (40 mL/L). Growth parameters observed included plant height, stem diameter, and number of leaves up to 12 Weeks After Planting (WAP). ANOVA analysis showed no statistically significant effect of the treatments on any parameter. However, descriptive data indicated that concentrations of 20–30 mL/L tended to produce better growth: P2 (31.25 cm) had the highest plant height, P3 (6.93 mm) the highest stem diameter, and P1 (12 leaves) the most leaves. Chitosan potentially acts as a plant growth stimulator by increasing nitrogen availability and enhancing physiological processes such as photosynthesis. In contrast, a high concentration (40 mL/L) exhibited inhibitory effects. Although the differences were not statistically significant, concentrations of 20–30 mL/L could be recommended for practical application. The lack of significant results may be attributed to suboptimal concentrations, application frequency, or environmental conditions. Further studies are recommended to modify treatments and assess additional parameters such as biomass, root development, and leaf area to better understand the efficacy of chitosan fertilizer in cocoa seedling growth.